2021
DOI: 10.18632/aging.202744
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of CRBN induces loss of type I collagen and SCH in mouse skin by fibroblast senescence via the p38 MAPK pathway

Abstract: Cereblon (CRBN) is a substrate receptor of the cullin-RING E3 ubiquitin ligase (CRL) complex that mediates the ubiquitination of several substrates. In this study, CRBN knockout (KO) mice exhibited decreased levels of stratum corneum hydration (SCH) and collagen I expression with an elevated protein level of matrix metalloprotease 1 (MMP1). The absence of cereblon in the skin of CRBN KO mice mimics the damage caused by narrowband ultraviolet B (NB-UVB). The primary CRBN deficient mouse embryonic fibroblasts (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The relationship pair with the greatest difference (0.08172) was CRBN–MRPL40 ( Table 5 ). CRBN functions as a potential regulator of cell homeostasis by mediating the ubiquitination of target substrates involved in processes including ion transport, the AMP-activated protein kinase (AMPK) signaling pathway, and cellular metabolisms ( Shi and Chen, 2017 ; Jeon et al, 2021 ). It also protects cells from fat metabolism disorders (induced by high-fat levels) and negatively regulates CD4 + T cell activation ( Shi and Chen, 2017 ), and has been implicated in a variety of diseases including CVD, obesity, and fatty liver ( Shi and Chen, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship pair with the greatest difference (0.08172) was CRBN–MRPL40 ( Table 5 ). CRBN functions as a potential regulator of cell homeostasis by mediating the ubiquitination of target substrates involved in processes including ion transport, the AMP-activated protein kinase (AMPK) signaling pathway, and cellular metabolisms ( Shi and Chen, 2017 ; Jeon et al, 2021 ). It also protects cells from fat metabolism disorders (induced by high-fat levels) and negatively regulates CD4 + T cell activation ( Shi and Chen, 2017 ), and has been implicated in a variety of diseases including CVD, obesity, and fatty liver ( Shi and Chen, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that CRBN is a potential regulator of the skin barrier's function and dermal homeostasis, demonstrating a significant decrease in collagen I secretion into the extracellular space with an elevated protein expression of matrix metalloprotease 1 in CRBN KO mouse skin [8]. In addition, stratum corneum hydration (SCH) analyses revealed impaired skin barrier function caused by the loss of CRBN in the mouse skin tissues ex vivo [8]. Therefore, we further investigated the role of CRBN in mouse skin by optical assessment with second harmonic generation (SHG) microscopy, which is highly sensitive in detecting dermal collagen fibers in the skin.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that CRBN is a potential regulator for skin barrier function and dermal homeostasis, revealing that the skin phenotype of CRBN ablated mice was similar to skin damaged by narrowband ultraviolet B (NB‐UVB). In detail, the CRBN ablated mice skin exhibited decreased protein expression of dermal collagen with altered protein signaling via cellular senescence in fibroblast [8]. In addition, CRBN deletion prevents high‐fat diet‐induced obesity in mice and exhibits noticeable changes in the gene expression of lipogenesis and lipid metabolism coordinated by AMP‐activated protein kinase(AMPK) [9].…”
Section: Introductionmentioning
confidence: 99%
“…JNK transduces the signal to AP-1 and mediates MMP-3, IL-6, and IL-8 expression ( Song et al, 2019 ). p38 MAPK induces premature senescence phenotype in skin fibroblasts and downregulates COL1A1 ( Jeon et al, 2021 ). Like other natural substances from Dendrobium nobile Lindl., UCP withheld MGO-induced fibroblast senescence by suppressing the JNK/c-Jun/MMPs and p38/NF-κB/COL1A1 axes ( Bigot et al, 2012 ; Terazawa et al, 2021 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%